Difference harmonic generation due to spin-flip transitions in an asymmetric quantum well - Korovin, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The difference harmonic generation in an asymmetric quantum well based on AlSb/InSb heterostructures has been calculated. The intersubband electron spin-flip transitions are analyzed in the framework of the three-band Kane model. Numerical results for the spectral dependencies of a nonlinear susceptibility under of a double resonance conditions for CO₂ laser have been obtained.